2022
DOI: 10.3390/jcm11154451
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Effects of Oral Administration of Curcuma Longa and Boswellia Serrata Combination in Patients with Treatment-Naïve Diabetic Macular Edema

Abstract: Anti-vascular endothelial growth factor nowdays represents the standard of care for diabetic macular edema (DME). Nevertheless, the burden of injections worldwide has created tremendous stress on the healthcare system during the COVID-19 pandemic. The aim of this study was to investigate the effects of the oral administration of Curcuma longa and Boswellia serrata (Retimix®) in patients with non-proliferative diabetic retinopathy (DR) and treatment-naïve DME < 400 mm, managed during the COVID-19 pandemic. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…It was shown that this combined approach resulted in improved visual acuity and a reduction in DME [33]. At the same time, Guarino et al documented the effectiveness of Curcuma longa and Boswellia serrata in individuals diagnosed with NPDR and who were treatment-naïve, and their findings indicated that these interventions were successful in preserving baseline CMT and best-corrected visual acuity BCVA values throughout the duration of the study [34].…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that this combined approach resulted in improved visual acuity and a reduction in DME [33]. At the same time, Guarino et al documented the effectiveness of Curcuma longa and Boswellia serrata in individuals diagnosed with NPDR and who were treatment-naïve, and their findings indicated that these interventions were successful in preserving baseline CMT and best-corrected visual acuity BCVA values throughout the duration of the study [34].…”
Section: Discussionmentioning
confidence: 97%